Advances in liver engineering with cell, scaffold, and vascularization - Chunyan Liu; Yulian Wang; Xuqian Zhou; Lei Dong (EngMedicine)
Liver tissue engineering is a promising alternative to organ transplantation for the treatment of end-stage liver disease, acute liver failure, and liver-based metabolic disorders. This review discusses the current progress and obstacles in tissue engineering of cell sources, biomaterials, and vascularization strategies, which are key to constructing functional liver tissues. Significant progress has been made in developing available cell sources, tunable biomaterials, and integrating vascular networks. However, challenges remain in replicating the complex architecture and function of the liver. Further research is required to overcome these hurdles and ultimately realize the full potential of tissue-engineered liver constructs in clinical applications.